Bifurcation of Limit Cycles of a Perturbed Pendulum Equation (Journal of Nonlinear Modeling and Analysis, 2024)
This paper investigates the limit cycle bifurcation problem of thependulum equation on the cylinder of the form $\dot{x} = y, \dot{y} = − {\rm sin} x$ under perturbations of polynomials of ${\rm sin} x,$ ${\rm cos} x$ and $y$ of degree $n$ with a switchingline $y = 0.$ We first prove that the corresponding first order Melnikov functions can be expressed as combinations of anti-trigonometric functions and thecomplete elliptic functions of first and second kind with polynomial coefficientsin both the oscillatory and rotary regions for arbitrary $n.$ We also verify theindependence of coefficients of these polynomials. Then, the lower bounds forthe number of limit cycles are obtained using their asymptotic expansions with $n = 1, 2, 3.$
Keywords: Pendulum equation; complete elliptic function; Melnikov function; limit cycle.